Reactions to some ICT-based personnel selection tools - Balcerak, Alicja; Woźniak, Jacek (Economics & sociology, 2021)
If human resource management (HRM) tools based on information technologies (ICT) are to support organizational effectiveness, it is imperative that these tools are accepted by employees. Knowledge concerning how ICT-based selection tools are perceived by potential employees is limited, which was the impulse for this research. A standard methodology for studies into fairness assessment of recruitment tools was followed here. Descriptions were prepared for five new ICT-based selection tools (long-distance synchronic interview; game results and analysis of candidates’ behaviour while playing a computer game; gathering information over the internet in the form of content-based analytics and structure-based analytics). Data from 833 Polish candidates collected using an e-questionnaire showed that fairness assessment for the five new selection tools is lower than for their traditional counterparts, i.e., interview, work samples, references and biodata questionnaire. It was also shown that the internet experience — measured by frequency of its use — and belonging to a younger generation do not significantly affect higher acceptance of ICT-based methods. The article indicates what kinds of activities may be undertaken to increase this acceptance.